Utility of Saline-Induced Resting Full-Cycle Ratio Compared with Resting Full-Cycle Ratio and Fractional Flow Reserve. (7th April 2020) - Sato, Takao; Goto, Sonoka; Ohta, Yusuke; Taya, Yuji; Yuasa, Sho; Takahashi, Minoru; Okabe, Masaaki; Aizawa, Yoshifusa
Abstract : Background . The saline-induced distal coronary pressure/aortic pressure ratio predicted fractional flow reserve (FFR). The resting full-cycle ratio (RFR) represents the maximal relative pressure difference in a cardiac cycle. Therefore, the present study aimed to compare the results of saline-induced RFR (sRFR) with FFR. Methods . Seventy consecutive lesions with only moderate stenosis were included. The FFR, RFR, and sRFR values were compared. The sRFR was assessed using an intracoronary bolus infusion of saline (2  mL/s) for five heartbeats. The FFR was obtained after an intravenous injection of papaverine. Results . Overall, the FFR, sRFR, and RFR values were 0.78 ± 0.12, 0.79 ± 0.13, and 0.83 ± 0.14, respectively. With regard to anatomical morphology were 40, 18, and 12 cases of focal, diffuse, and tandem lesion. There was a significant correlation between the sRFR and FFR ( R  = 0.96, p < 0.01 ). There were also significant correlations between the sRFR and FFR in the left coronary and right coronary artery ( R  = 0.95, p < 0.01 and R  = 0.98, p < 0.01 ). Furthermore, significant correlations between sRFR and FFR were observed in not only focal but also in nonfocal lesion including tandem and diffuse lesions ( R  = 0.93, p < 0.01 and R  = 0.97, p < 0.01 ). A close agreement on FFR and sRFR was shown using the Bland–Altman analysis (95% CI of agreement: −0.08–0.07). In the receiver operating characteristic curve analysis, the cutoff value of sRFR to predict an FFR of 0.80 was 0.81 (area under curve, 0.97; sensitivity 90.6%; and specificity 98.2%). Conclusion . The sRFR can accurately and safely predict the FFR and might be effective for diagnosing ischemia.